OPTOELECTRONNICS FUNCTION AND ALGORITHM-SPECIFIC INFORMATIVE DEVICES ON THE BASIS OF DIGITAL SYGNAL PROCESSORS - Lytvyn, Igor; Valeriy Martynyuk, Valeriy (International Journal of Computing, 2014)
Presented analysis of influence of parameters and descriptions on informative processes passing in Optoelectronics Function and Algorithm-Specific Informative Devices units for providing a rational choice of information flow diagrams and hardware for their realization under the concrete task.